Evaluation of the influence of the state of environmental security of the population of Kyiv on the level of morbidity - Kirova, M. (Land Management, Cadastre and Land Monitoring, 2017)
The influence of atmospheric air pollution on the health status of the city of Kiev has been monitored. A direct relationship between the increase in the concentration of harmful substances in the atmospheric air of the contaminated area and the increase in the incidence of the population, including diseases of the respiratory system, circulatory systems, blood and blood-forming organs, endocrine, nervous systems is established.Problems of ensuring environmental safety are traditionally among the priority areas of state-legal regulation. National environmental policy is aimed at achieving the strategic goals: preservation of natural objects and complexes, ecosystems, maintenance of their integrity and life support functions, sustainable development of society, improvement of the quality of environment and life, improvement of population health and demographic situation, provision of environmental safety state. And this is possible only in carrying out the assessment and consistent reduction of environmental risks for human health. There is a high risk of emergencies of natural and man-made nature in Ukraine. In Ukraine there are 23,767 potentially dangerous enterprises and other objects, the accidents on each of which can lead to emergencies of anthropogenic and natural state, regional, local and object level. Each year, up to 300 emergencies of natural and man-made nature are recorded, resulting in death of people, causing significant economic losses. Environmental policy in modern conditions is considered as an integrated factor of social and economic development of Ukraine, which helps to ensure the transition to sustainable development of the economy and the introduction of an environmentally balanced system of nature use.Provision of environmentally and technogenically safe living conditions of citizens and society, preservation of the natural environment and rational use of natural resources is assigned by the Law of Ukraine "On the Fundamentals of National Security of Ukraine" to the priorities of the national interests of Ukraine (Article 6).The environment is considered safe when its state meets the criteria, standards, limits and norms, established in the legislation, concerning its purity (non-contamination), resource intensity (non-extinction), environmental sustainability, sanitary requirements, species diversity, and ability to satisfy citizens' interests.Today there is an increase in anthropogenic impact on the atmosphere, which is manifested mainly due to its pollution, and therefore inevitably affects the state of ecosystems and human health. That is why the study of problems associated with atmospheric air pollution - an extremely important natural component of human life and human life - is now becoming particularly acute and urgent. At present, the total air pollution in the large and medium-sized cities of Ukraine is 2-4 times higher than the permissible level and is dangerous for the health of the population. Consequently, the problems of ensuring environmental safety for the population of Kyiv, as many large cities of Ukraine, are very relevant.In connection with this, the article establishes a direct relationship between the increase in the concentration of harmful substances in the air of the contaminated area and the increase in the incidence of the population in the context of environmental safety.Keywords. Environmental safety, anthropogenic influence, atmospheric air, pollutants, pollution level, health status of the population, the incidence of the population.